Defect‐Engineered n‐Doping of WSe2 via Argon Plasma Treatment and Its Application in Field‐Effect Transistors. Issue 14 (27th June 2021) - Kim, Junghun; Park, Hyunik; Yoo, SangHyuk; Im, Yeon‐Ho; Kang, Keonwook; Kim, Jihyun
Abstract: Doping of van der Waals layered semiconductor materials is an essential technique to realize their full potential for implementation in nanoelectronics. Herein, defect‐engineered and area‐selective n‐doping of ambipolar multi‐layer WSe2 are demonstrated via Ar plasma treatment. The contact regions of the WSe2 are exposed to a mild Ar plasma treatment to induce Se vacancy, while the channel region is protected by a hexagonal boron nitride. The results are systematically analyzed using structural and optical characterization methods, and the origin of the n‐type properties in the plasma‐treated WSe2 is proposed using plane‐wave density functional theory calculations. The formation of a defect‐induced donor level in the source and drain regions of the multi‐layer WSe2 helps to improve the contact behaviors in field‐effect transistors (FETs), enhancing the transport of the free electrons. The n‐channel current on/off ratio (from 12.8 to 8.3 × 10 6 ) and contact resistance (as low as 2.68 kΩ∙mm) of the n‐type WSe2 FETs are greatly improved by the area‐specific Ar plasma treatment, enabling the fabrication of a WSe2 ‐based complementary metal‐oxide‐semiconductor inverter. This method provides a viable route to control the carrier type and concentration in ambipolar van der Waals layered semiconductors, paving the way for high‐performance nanoelectronic devices. Abstract : Defect‐engineered and area‐selective n‐doping of ambipolar layered WSe2 are demonstrated via Ar plasma treatment. The formation of a defect‐induced donor level improved the contact behaviors in field‐effect transistors, enhancing the transport of free electrons. The n‐channel current on/off ratio and contact resistance are greatly improved by area‐specific Ar plasma, enabling the fabrication of a WSe2 ‐based complementary metal‐oxide‐semiconductor inverter.